1999
DOI: 10.1182/blood.v94.10.3315.422k16_3315_3324
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Treatment of Acute Promyelocytic Leukemia With Arsenic Trioxide: Remission Induction, Follow-Up, and Molecular Monitoring in 11 Newly Diagnosed and 47 Relapsed Acute Promyelocytic Leukemia Patients

Abstract: Fifty-eight acute promyelocytic leukemia (APL) patients (11 newly diagnosed and 47 relapsed) were studied for arsenic trioxide (As2O3) treatment. Clinical complete remission (CR) was obtained in 8 of 11 (72.7%) newly diagnosed cases. However, As2O3 treatment resulted in hepatic toxicity in 7 cases including 2 deaths, in contrast to the mild liver dysfunction in one third of the relapsed patients. Forty of forty-seven (85.1%) relapsed patients achieved CR. Two of three nonresponders showed clonal evolution at r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
194
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 553 publications
(203 citation statements)
references
References 21 publications
2
194
0
3
Order By: Relevance
“…1 Previous studies indicated that patients in CR2 had poor long-term relapse-free survival rates of only 22% to 37%. 6,20,21 HSCT is conventionally regarded as a consolidation strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Previous studies indicated that patients in CR2 had poor long-term relapse-free survival rates of only 22% to 37%. 6,20,21 HSCT is conventionally regarded as a consolidation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Arsenic trioxide (As 2 O 3 ) delivered intravenously (intravenous As 2 O 3 ) is highly efficacious for APL in first relapse (R1), inducing second complete remission (CR2) in >90% of patients. 6,7 Similar to other acute myeloid leukemias, consolidation of CR2 with autologous or allogeneic hematopoietic stem cell transplantation (HSCT) is then recommended. 1 However, prospective data validating HSCT or other approaches as the optimal postremission therapy for APL in CR2 are not available.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 ATO alone or in combination with ATRA is an excellent option for older patients, who often cannot tolerate anthracycline-based therapy. [31][32][33][38][39][40] It will also be interesting to see the impact of ATO on the survival of this particular population in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic trioxide (ATO) is an antineoplastic chemotherapeutic agent approved for the treatment of relapsed or refractory acute promyelocytic leukaemia (APL; Niu et al, 1999;Soignet et al, 2001). The use of ATO to treat MM is supported by preclinical studies in which this agent has been shown to inhibit growth, reduce viability and induce apoptosis in several myeloma cell lines at concentrations that can be safely achieved in patients (Park et al, 2000;Perkins et al, 2000;Hideshima et al, 2002;Campbell et al, 2004a).…”
mentioning
confidence: 99%